The influence of personal knowledge in the teacher's profession - Francesco Lo Presti; Alessandra Priore (Firenze University Press, 2018)
The field of the teaching profession represents a field of work where the implicit dimensions of both the self and the context are key factors in concrete work. Such implicit dimensions do also influence and affect tacitly the representation of the professional role and the context. Moreover they direct the action in terms of ratings, choices, behaviors. The work describes a training and research experience, according to a narrative approach, which involved teachers of upper secondary school. The aim was to identify, on the one hand, the critical aspects that require an implementation of vocational training in critical and relational sense and, on the other hand, to highlight the validity of critical-reflexive pathways in the teachers' training.    L'influenza del sapere personale nella professione docente  L'ambito della professione docente costituisce un terreno di lavoro nel quale le dimensioni implicite di sé e del contesto costituiscono elementi determinanti nel prefigurare il fare lavorativo concreto, nonché forme di influenza che sagomano tacitamente le rappresentazioni del ruolo e del contesto professionale e che dirigono l'agire in termini di valutazioni, scelte, comportamenti. Il contributo riporta una esperienza di formazione e ricerca, secondo un approccio narrativo, che ha coinvolto docenti della scuola secondaria di secondo grado, finalizzata a cogliere, da un lato, le dimensioni problematiche che richiedono una implementazione della formazione professionale in senso critico e relazionale e, dall'altro, a partire da tali dimensioni, quello di evidenziare la validità di percorsi formativi critico-riflessivi nell'ambito della formazione professionale dei docenti.